Cytotoxic activity against prelabelled RTG-2 cells in the turbot, Scophthalmus maximus (L.) - Tafalla, Carolina; Figueras Huerta, Antonio; Novoa, Beatriz (Journal of Fish Diseases, 2001)
7 páginas, 5 figuras Leucocytes derived from head kidney, blood and spleen of turbot, Scophthalmus maximus (L.), exhibited cytotoxic activities against an established cell line (RTG-2) derived from rainbow trout, Oncorhynchus mykiss (Walbaum). The optimal effector:target ratio, temperature and incubation period for the activity was determined. Cytotoxicity was not caused by released factors, as effector:target contact was needed. Visualization of the cultures under the transmission electron microscope corroborated the contact between leucocytes and target cells and suggested the implication of monocyte-like cells in this cell-mediated cytotoxicity. This research was supported by grant MAR 96-1775 from the ComisioÂn Interministerial de Ciencia y TecnologõÂa (CICYT). Peer reviewed